Anionic subsite of active center of Torpedo acetylcholinesterase constructs a part of its conformational epitope - Fu Feng-Hua; Xin Yan-Bin; Li Feng-Zhen; Zhang Han; Sun Man-Ji (Acta Pharmacologica Sinica, 2016)
AIM: To study the structure-activity relationship of Torpedo acetylcholinesterase (AChE) and explore whether the anionic subsite of the active center is a constituent of the conformational epitope of enzyme. METHODS: Using ELISA and enzyme inhibition test to examine the effect of 1-methyl-2-hydroxyiminomethylpyridium chloride (2-PAM), an anionic subsite probe of AChE, on the immunoreactivity between Torpedo AChE and its monoclonal antibody (McAb) 3F3. RESULTS: McAb 3F3 did not react with 2-PAM-AChE complex. 2-PAM decreased the inhibitory rate of McAb 3F3 on AChE in a concentration-dependent fashion, but did not dissociate the McAb 3F3-AChE complex. CONCLUSION: Anionic subsite of the active center of Torpedo AChE constructs a part of its conformational epitope.